Level I Progressive Mobilization effected on Improvement Pulmonary Oxygenation Ventilation Function in Non Hemorrhagic Stroke Patients - Niken Setyaningrum; Mardiyono Mardiyono; Untung Sujianto (Alma Ata University Press, 2017)
Immobilization in non-hemorrhagic stroke patients can lower lung expansion due to an accumulation of secretions resulting in impaired oxygenation ventilation function of the lungs, thus facilitating the growth of bacteria that cause pneumonia. Switching the patient's position every 2 hours allows the lung area to re-expand and to increase the transport of oxygen which will improve oxygenation ventilation function of the lungs. Various research results concluded that a measure to prevent changes in the oxygenation ventilation function of the lungs is to maintain the airway effective. This can be done by putting the patient in a sloping or semi-prone position, heightening the head of the bed to a 30- degree angle. Level I progressive mobilization is a preferred intervention that is safe to do to maintain the lung's oxygenation ventilation function. Objective: To evaluate the effect of progressive mobilization of level I on the pulmonary oxygenation ventilation function in non-hemorrhagic stroke patients. Methods: Design of experimental research. Sampling was done using random allocation with the number of samples that were 52 people, using the Wilcoxon and Man Whitney test analysis. The results showed that the measurement of the pulmonary oxygenation ventilation function using the peak flow meter seen in the intervention group had a significant increase in air volume, from before the intervention of 220 ± 78,9 to 263,65 ± 61.6 after 5 days of intervention, with p-value <0.001. While in the control group there was a significant decrease of air volume from 255 ± 58,94 to 225 ± 53,16 with p-value <0.001. The oxygenation ventilation function average increase in the intervention group was 43.65, higher than the increase in the control group, which decreased by -30. The Mann Whitney test result obtained p-value <0.001. In conclusion. there was a significant difference in the pulmonary oxygenation ventilation functions in the intervention and control groups after the level I progressive mobilization in non- hemorrhagic stroke patients at Dr.Adhyatma Semarang Hospital, which means that there was an impact of the level I mobilization on the lung oxygenation ventilation function on non-hemorrhagic stroke patients in Dr. Adhyatma Semarang Hospital.